2019
DOI: 10.1002/ijc.32367
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin and 5‐fluorouracil: Effective combination for PIK3CA‐mutant colorectal cancer

Abstract: The normal colon epithelium is transformed into its neoplastic counterpart through a series of genetic alterations in driver genes including activating mutations in PIK3CA. Treatment often involves surgery followed by 5-fluorouracil (5-FU) based therapy, which has limited efficiency and serious side effects. We sought to determine whether fisetin, a dietary flavonoid, alone or in combination with 5-FU affected tumorigenesis in the mammalian intestine. We first determined the effect of fisetin, 5-FU or their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Fisetin (3,3’,4’,7-tetrahydroxyflavone), which distributes abundantly in vegetables, as well as fruits for instance cucumber, persimmon, and apple, was explored to possess antioxidant, anti-microbial, anti-cancer, as well as anti-inflammatory properties in recent studies [ 13 ]. For example, fisetin could dampen colorectal cancer cells growth in vitro along with in vivo [ 14 ] and display anti-cancer effects on laryngeal carcinoma [ 15 ]. However, there is no report about the anti-cancer influence of fisetin on PC.…”
Section: Introductionmentioning
confidence: 99%
“…Fisetin (3,3’,4’,7-tetrahydroxyflavone), which distributes abundantly in vegetables, as well as fruits for instance cucumber, persimmon, and apple, was explored to possess antioxidant, anti-microbial, anti-cancer, as well as anti-inflammatory properties in recent studies [ 13 ]. For example, fisetin could dampen colorectal cancer cells growth in vitro along with in vivo [ 14 ] and display anti-cancer effects on laryngeal carcinoma [ 15 ]. However, there is no report about the anti-cancer influence of fisetin on PC.…”
Section: Introductionmentioning
confidence: 99%
“…The combination determined inhibition of AKT phosphorylation and decreased PI3K (phosphatidylinositide-3-kinase) expression. A preventive effect against tumor formation was also observed for fisetin (Khan et al, 2019). Fisetin acts on oral squamous cell carcinoma by targeting PAK4 (p21-activated kinase 4).…”
Section: Sulfuretinmentioning
confidence: 78%
“…FIS causes a decrease in the viability of colorectal cancer cells of the HCT116 and HT29 lines [47][48][49][50][51], LoVo [52], COLO205 [49,50,53], HT-29 [47,49,51,54] and HCT-15 [51]. It has also been shown that in the case of HCT-116 and HT-29 lines, FIS reduces the number of colonies, and this effect may be maximized by combining FIS with 5-fluorocuacil (5-FU) [47,50].…”
Section: Activity Toward Colorectal Cancer Cellsmentioning
confidence: 99%